Strategic management planning for domestic & global competition - Pearce, John A. (Strategic management)
Contemporary research in strategic management, with an emphasis on conceptual tools and skills created by scholars and practitioners in the field are evident throughout Strategic Management, 13e. This thirteenth edition of Strategic Management has a refined message and a new subtitle: Planning for Domestic & Global Competition. This new edition is specially designed to accommodate the needs of strategy students worldwide in our fast-changing twenty-first century. The authors complement the focus on strategic planning for success within U.S. borders with unprecedented attention on how U.S. firms can leverage their domestic success by forming international partnerships and can achieve international success by becoming actively involved in global trade. These are exciting times, and they are reflected in this book. The new edition includes NEW or revised chapter material, 30 NEW cases, and dozens of NEW illustrations.